Phylogenomic Analyses and Comparative Studies on Genomes of the Bifidobacteriales: Identification of Molecular Signatures Specific for the Order Bifidobacteriales and Its Different Subclades - Zhang, Grace; Gao, Beile; Adeolu, Mobolaji; Khadka, Bijendra; Gupta, Radhey S. (Frontiers in Microbiology, 2016)
The order Bifidobacteriales comprises a diverse variety of species found in the gastrointestinal tract of humans and other animals, some of which are opportunistic pathogens, whereas a number of others exhibit health-promoting effects. However, currently very few biochemical or molecular characteristics are known which are specific for the order Bifidobacteriales, or specific clades within this order which distinguish them from other bacteria. This study reports the results of detailed comparative genomic and phylogenetic studies on 62 genome-sequenced species/strains from the order Bifidobacteriales. In a robust phylogenetic tree for the Bifidobacteriales constructed based on 614 core proteins, a number of well-resolved clades were observed including a clade separating the Scarodvia-related genera (Scardovia clade) from the genera Bifidobacterium and Gardnerella, as well as a number of previously reported clusters of Bifidobacterium spp. In parallel, our comparative analyses of protein sequences from the Bifidobacteriales genomes have identified numerous molecular markers that are specific for this group of bacteria. Of these markers, 32 conserved signature indels (CSIs) in widely distributed proteins and 10 signature proteins are distinctive characteristics of all sequenced Bifidobacteriales species and provide novel and highly specific means for distinguishing these bacteria. In addition, multiple other molecular signatures are specific for the following clades of Bifidobacteriales: (i) 5 CSIs specific for a clade comprising of the Scardovia-related genera; (ii) 3 CSIs and 2 CSPs specific for a clade consisting of the Bifidobacterium and Gardnerella spp.; (iii) multiple other signatures demarcating a number of clusters of the B. asteroides-and B. longum- related species. The described molecular markers provide novel and reliable means for distinguishing the Bifidobacteriales and a number of their clades in molecular terms and for the classification of these bacteria. The Bifidobacteriales-specific CSIs, found in important proteins, are predicted to play important roles in modifying the cellular functions of the affected proteins. Hence, biochemical studies on the cellular functions of these CSIs could lead to discovery of novel characteristics of either all Bifidobacteriales, or specific groups of bacteria within this order. Some of the functions affected/modified by these genetic changes could also be important for the probiotic/pathogenic activities of the bifidobacteria.